2014
DOI: 10.1007/s00253-014-5796-2
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of chemical scrubbers to biotrickling filters for VOCs and H2S treatment at low contact times

Abstract: The purpose of this work was to evaluate the technical and economical feasibility of converting three in-series chemical scrubbers to biotrickling filters for the simultaneous removal at neutral pH of 10000 m 3 /h containing H 2 S and volatile organic compounds (VOCs) at a wastewater treatment plant (WWTP). The conversion was based on previous conversion protocols and mainly required of replacing the original packing material by a structured packing and recycle pumps, besides modifying the controls and operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…Although lab‐scale BTFs are commonly provided with additional mechanical or magnetic stirring in the holding tank, this practice is quite difficult to implement in full‐scale BTFs as it would compromise the economic feasibility of the treatment technology. As a matter of fact, recent reports on air pollution control by means of full‐scale BTFs do not even consider the use of additional mechanical mixing in the holding tank . Under this scenario, knowledge of the parameters affecting the mass transfer and mixing performance of full‐scale BTFs become of paramount importance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lab‐scale BTFs are commonly provided with additional mechanical or magnetic stirring in the holding tank, this practice is quite difficult to implement in full‐scale BTFs as it would compromise the economic feasibility of the treatment technology. As a matter of fact, recent reports on air pollution control by means of full‐scale BTFs do not even consider the use of additional mechanical mixing in the holding tank . Under this scenario, knowledge of the parameters affecting the mass transfer and mixing performance of full‐scale BTFs become of paramount importance.…”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, recent reports on air pollution control by means of full-scale BTFs do not even consider the use of additional mechanical mixing in the holding tank. [26][27][28] Under this scenario, knowledge of the parameters affecting the mass transfer and mixing performance of full-scale BTFs become of paramount importance. The results herein obtained showed that relatively short packed columns (1.8 ≤ H/D ≤ 3.2) will support higher mass transfer and mixing performance compared with tall columns (e.g.…”
Section: H/d Ratio As a Key Design Parameter For Btfsmentioning
confidence: 99%
“…This scenario is common in wastewater treatment plants where the air stream has a higher concentration of hydrogen sulphide compared to ammonia [1,39]. There are several examples in the literature of full scale conversion of chemical scrubbers into biological systems for the treatment of gases in wastewater treatment plants [36,[54][55][56]. A convenient ten step protocol was developed by Deshusses and his coworkers as a general procedure for the conversion of chemical scrubbers to biofilters in WWTP [37,55].…”
Section: Full Scale Conversion Of Chemical Scrubber To Biofilter Setupmentioning
confidence: 99%
“…For the microorganisms to operate at optimal performance, the pH of the biofilter in WWTP is typically maintained by washing the biofilter with chemicals or a buffered solution [19,23,36]. In an industrial scale biofilter, this leads to production of large volumes of leachate which contains ions like SO4 2-, NO2 -and NO3 -which needs to be measured and the leachate requires proper disposal [18,19,37].…”
Section: -) Examples Of Sob Include Thiobacillus Denitrificans Thimentioning
confidence: 99%
“…mg C m-3 ) progressively hindered the RE up to a value of 53% at an inlet concentration of 1100 mg m -3 (1014 mg C m -3 ).At this point it is important to stress that biological air treatment technologies are nowadays challenged by industrial end-users to improve the economic feasibility in terms of investment costs[23]. Thus, although an EBRT of 30 s is one of the shortest gas residence times yielding high and stable styrene REs in BTFs further optimization in terms of EBRT is still necessary to reduce the size of the BTF and, consequently, reduce the investment cost of the treatment technology[24].…”
mentioning
confidence: 99%